2007
DOI: 10.1002/ijc.23219
|View full text |Cite
|
Sign up to set email alerts
|

MGMT in primary and recurrent human glioblastomas after radiation and chemotherapy and comparison with p53 status and clinical outcome

Abstract: The DNA repair protein O 6 -methylguanine-DNA methyltransferase (MGMT) plays a pivotal role in alkylating drug resistance. Here, we determined MGMT activity in primary and recurrent glioblastomas (GBM, WHO grade IV) of patients who received radiation therapy (RT) or RT plus chemotherapy with alkylating agents (temozolomide, chloroethylnitrosoureas). The mean MGMT activity of untreated GBM was 37 6 45 (range 0-205) fmol/mg proteins. In the 1st, 2nd and 3rd recurrences, MGMT activity increased from 66 6 50 (13-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 49 publications
(78 reference statements)
10
91
1
1
Order By: Relevance
“…Nevertheless, we did not detect a significant cooperative effect of MGMT hypermethylation and lack of TP53 mutation in terms of longer TTP after initiation of chemotherapy and longer OS in our patient cohort. The finding of MGMT protein expression not being significantly different between TP53 mutant and wild-type glioblastomas is in line with a recent study that reported no relationship between MGMT protein expression and p53 immunostaining (22). Thus, our results do not support the hypothesis that low MGMT expression is associated with increased p53 immunopositivity in glioblastomas (23).…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, we did not detect a significant cooperative effect of MGMT hypermethylation and lack of TP53 mutation in terms of longer TTP after initiation of chemotherapy and longer OS in our patient cohort. The finding of MGMT protein expression not being significantly different between TP53 mutant and wild-type glioblastomas is in line with a recent study that reported no relationship between MGMT protein expression and p53 immunostaining (22). Thus, our results do not support the hypothesis that low MGMT expression is associated with increased p53 immunopositivity in glioblastomas (23).…”
Section: Discussionsupporting
confidence: 64%
“…Although consideration of the extent of methylation allows greater prognostic stratification, a single cut-off in methylation derived from a quantitative assay may be more useful in the clinic. Wiewrodt et al (Wiewrodt et al, 2008) showed that patients expressing p30 fmol mg À1 MGMT protein in the pre-treatment tumour volume had a significantly better response to alkylating therapy than those with MGMT protein above this level. Others have shown that patients with low MGMT protein expression had significantly improved survival compared with those with high expression (Brell et al, 2005;Chinot et al, 2007;Nagane et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…By means of an assay that measured the transfer of 3 Hlabeled methyl groups from the O 6 position of guanine to protein in the cell extract, MGMT activity was shown to be increased in recurrent tumors specifically in patients who had received alkylating agent chemotherapy. 21,22 However, such data have not been generated in a controlled, prospective manner and with parallel assessment of MGMT promoter methylation.…”
Section: Enzyme Activitymentioning
confidence: 99%